The Analysis of Indonesian EFL Argumentative Writing Using Toulmin’s Model: The Structure and Struggles from the Learners - Hanna Sundari; Rina Husnaini Febriyanti (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
Argumentative writing plays an important role in academic writing at university level. However, learners mostly find that writing this essay a challenging and effortful task. This present study aims at exploring the structures of argumentative essay written by Indonesian EFL students from one university in Jakarta Indonesia. Moreover, it investigates their difficulty and constraints during composing the essay. Using a descriptive qualitative design, the authors selected writing assignment and questionnaire for collecting data. A layout of Toulmin model of arguments was used in analyzing the essays. The findings of the study show that the argumentative papers cover the main elements: claim (thesis statement), data, rebut, and rebuttal data using either in block pattern or point-by-point pattern. The elements show diverse in types. Logical analysis and explanation are the most frequently used on the papers. Though they present acceptable thesis with well-organized essay, some information is unrelated and data for supporting the claim are seemingly insufficient. In addition, the students think that this essay as difficult task. In general, lack of knowledge, vocabulary and practice cause the constraints. In specific level, the students report that giving argument, finding support and working on counterargument become source of difficulty and constraints.